Carnap and Husserl in Debate - Caterina Del Sordo (Humana.Mente: Journal of Philosophical Studies)
This paper develops a particular Florentine perspective through which the contemporary debate on the relationship between Rudolf Carnap's philosophy and Edmund Husserl's phenomenology can be approached. The Florentine perspective combines transformative attitude and explicative method in philosophy. More specifically, the paper highlights the distinguishing features according to which Paolo Parrini's position on the relationship between Carnap's and Husserl's philosophies can be identified within Carnap scholarship. For this purpose, a phenomenology free of ontological-metaphysical presuppositions is elaborated by establishing its necessary conditions in revisiting material a priori statements. The paper reinterprets material a priori statements as those of neutral monism’s ideal umbrella theory and proposes Machian anti-metaphysics as a third way between the philosophies of Carnap and Husserl.